Poleward force at the kinetochore in metaphase depends on the number of kinetochore microtubules (The Rockefeller University Press, 1990)
To examine the dependence of poleward force at a kinetochore on the number of kinetochore microtubules (kMTs), we altered the normal balance in the number of microtubules at opposing homologous kinetochores in meiosis I grasshopper spermatocytes at metaphase with a focused laser microbeam. Observations were made with light and electron microscopy. Irradiations that partially damaged one homologous kinetochore caused the bivalent chromosome to shift to a new equilibrium position closer to the pole to which the unirradiated kinetochore was tethered; the greater the dose of irradiation, the farther the chromosome moved. The number of kMTs on the irradiated kinetochore decreased with severity of irradiation, while the number of kMTs on the unirradiated kinetochore remained constant and independent of chromosome-to-pole distance. Assuming a balance of forces on the chromosome at congression equilibrium, our results demonstrate that the net poleward force on a chromosome depends on the number of kMTs and the distance from the pole. In contrast, the velocity of chromosome movement showed little dependence on the number of kMTs. Possible mechanisms which explain the relationship between the poleward force at a kinetochore, the number of kinetochore microtubules, and the lengths of the kinetochore fibers at congression equilibrium include a "traction fiber model" in which poleward force producers are distributed along the length of the kinetochore fibers, or a "kinetochore motor-polar ejection model" in which force producers located at or near the kinetochore pull the chromosomes poleward along the kMTs and against an ejection force that is produced by the polar microtubule array and increases in strength toward the pole.